Knowledge, Attitude and Practice of Hepatitis B Vaccination among Health Care Workers at Manipal Teaching Hospital - Bhattarai, S. (Kathmandu University Medical Journal, 2020)
Background Hepatitis B vaccine is the single most effective and safest strategy for the prevention of the disease among health care workers. Despite the knowledge, higher occupational risk among themselves and increasing prevalence of hepatitis B virus worldwide, there is scanty information on knowledge, attitude and practice (KAP) concerning HBV vaccination among health care workers in our country.Objective To understand the knowledge, attitude and practice of hepatitis B vaccination among health care workers at Manipal Teaching Hospital at Pokhara, Gandaki Province in Nepal.Method Four hundred and eight health care workers were enrolled for an observational, cross-sectional study at Manipal Teaching Hospital, Gandaki Province, Nepal after obtaining ethical clearance from Institutional Review Committee. Pre-tested questionnaire including knowledge, attitude and practice regarding hepatitis B vaccination were studied.Result All participants demonstrated good knowledge and positive attitude towards Hepatitis B infection and vaccination. However many had risky practice towards it. Only about half (51.7%) of these participants were completely vaccinated. The most common reason for non vaccination was negligence.Conclusion Despite good knowledge and positive attitude towards hepatitis B infection and vaccination, low rates of vaccination and risky practice was observed among HCW. Various occupational, behavioural, economical and psychological factors associated with it must be explored. Easy availability of vaccine, regular hepatitis B campaigns must be conducted and policy guidelines need to be formulated by the government to manage all aspects of knowledge, attitude and practice of HCWs regarding hepatitis B vaccination.